Control of cucumber downy mildew disease under greenhouse conditions using biocide and organic compounds via induction of the antioxidant defense machinery - Amr Abdelfatah; Yasser S. A. Mazrou; Ramadan A. Arafa; Abeer H. Makhlouf; Asmaa El-Nagar (Scientific Reports)
Abstract Cucumber as an important vegetable crop faces a variety of abiotic and biotic stresses, especially the recently appeared fungicide-resistant strains of Pseudoperonospora cubensis, the causal agent of downy mildew disease. Herein, the present study aimed to evaluate the effect of Trichoderma asperellum strain T34 as a biological commercial product and potassium phosphite (KPHI) against P. cubensis and investigate the ability of these compounds to activate the plant defense system to suppress P. cubensis infection. In two separate experiments, the foliar applications with T34 or KPHI significantly reduced the severity of downy mildew disease and the area under the disease progress curve compared to water control. Scanning electron microscopy (SEM) of P. cubensis treated with T34 and KPHI showed shrunken and distorted sporangiophores and sporangia. Moreover, two tested compounds enhanced cucumber plants’ growth and yield parameters under greenhouse conditions. The tested compounds protected the membrane permeability of infected cucumber leaves and significantly reduced electrolyte leakage (EL %) compared to water control. These findings were associated with activating enzymatic antioxidant enzymes (catalase, peroxidase, and polyphenol oxidase). Our findings suggest that T34 and KPHI can be environmentally safe alternatives to chemical fungicides to control downy mildew disease in cucumber and other cucurbit crops.